Climate change and the life cycle of aedes mosquitoes as vectors of the dengue virus: A scoping review - Ginting, Gita Br; Sitorus, Angel Juliana Peace; Pane, Putri Yunita; Hartono; Simangungsong, Pahala Maringan Jubel (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Background: Climate change significantly impacts the epidemiology of vector-borne diseases. Dengue, transmitted by Aedes mosquitoes, is highly sensitive to climatic shifts, and global cases are surging. A clear understanding of how rising temperatures affect vector bionomics is essential for public health. This scoping review aims to synthesize recent evidence (2018–2025) on the relationship between climate change, particularly temperature, and the Aedes life cycle and dengue transmission. Methods: We conducted a scoping review using the Xiao and Watson (2019) framework. Systematic searches were performed in Scopus, PubMed, and Google Scholar for experimental, modeling, and field studies published between 2018 and 2025. Following screening based on predefined inclusion and exclusion criteria, 13 studies were included. Data were extracted and synthesized qualitatively to identify key themes. Results: The findings reveal a complex, non-linear thermal relationship. Vector fitness (e.g., survival, fertility) peaks at 25°C–30°C but declines under